Intersectional identities : influences of religion, race, and gender on the intimate relationships of single Singaporean Malay-Muslim women - Zainal, Humairah (2019)
Studies on rising singlehood in Asia have largely focused on the economic dimension. This article widens that lens by examining how religious beliefs influence single Singaporean women’s views toward marriage. Applying the intersectional paradigm expands our understanding of how religion maintains or challenges cultural norms as well as gendered and racial meanings. Drawing on in-depth interviews with 27 unmarried Malay-Muslim Singaporean women, it argues that instead of conceptualizing religion as a barrier that hinders the formation of intimate relationships, we can better understand its role in terms of how single Malay-Muslim women appropriate it to negotiate cultural constraints that limit their ability to tie the knot. The research bears important implications on how cultural and religious forces affect marriage patterns in multicultural and multireligious societies.